Edukasi Posyandu Remaja untuk Meningkatkan Pengetahuan Kesehatan Remaja di Desa Siboi - Arniawan; Sabir; Dwi Novriani Lumentah; Moh. Alfaridzi; Nita; Nurkumalasari Bahtiar; Nurul Auliyah Ramadhani; Rafli Saputra; Rezki Amrullah; Ririn Dwi Pratiwi; Vivit Novelin Kalara; Elvyka R. Yolimpat; Indah Fitri Lestari; Laila Ummu Fadhilah; Mellyani Labawo; Nurul Izzati (ABDI WIDYA NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Adolescence is a transitional phase from childhood to adulthood characterized by physical, emotional, and social changes. Insufficient understanding of these changes, combined with environmental influences, may contribute to the emergence of risk behaviors that lead to various adolescent health problems. This community service activity aimed to provide adolescent integrated health post (Posyandu Remaja) education to improve adolescents’ health knowledge. The methods employed included lectures, discussions, leaflet distribution, and role-playing of adolescent health service activities. The activity was conducted in Siboi Village on November 24, 2024, involving 12 adolescents as respondents. Evaluation results showed that, at the pre-test stage, most respondents had a low level of knowledge (7 respondents; 58.4%). After the educational intervention, post-test results indicated an improvement in knowledge, with the majority of respondents reaching a good level of knowledge (10 respondents; 83.3%). These findings demonstrate that the health education program significantly improved adolescents’ knowledge compared to before the intervention. In conclusion, adolescent integrated health post education is effective in increasing adolescents’ knowledge and can serve as a promotive and preventive strategy for improving adolescent health.